Partai Politik sebagai Utilitas Publik dalam Demokrasi di Indonesia - Lesmana, Chandra; Suryadi, Karim; Anggraeni, Leni (Jurnal Publisitas, 2021)
Political parties are an important pillar in a democratic system. In Indonesia, political parties receive budget assistance from the state, this is intended so that political parties can carry out their functions properly. Therefore, the researcher conducted a literature review to examine how political parties as public utilities in democracy in Indonesia. Researchers conducted a review of articles to observe the role of political parties as public utilities. The results of this review show that political parties that are given budget assistance by the state must have utilities for the community, one of which is political education. Overall, this review provides an appropriate reference for further research by identifying the role of political parties as public utilities, seen from how political parties obtain large budgets from the state to carry out their functions properly.